2012
DOI: 10.4028/www.scientific.net/amr.503-504.813
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of a Misaligned Rotor System with Asymmetric Shaft Stiffness

Abstract: Vibration characteristics of a misaligned rotor with asymmetric shaft stiffness are studied. The system consists of two shafts connected by a flexible coupling with parallel misalignment, two rigid disks attached at the middle of each shaft and one of the shafts has asymmetric stiffness. The governing ordinary differential equations are derived using Lagrange dynamics and integrated through numerical methods. The effects of asymmetry, eccentricity and misalignment are studied through the peak-to-peak lateral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Feng et al [25] investigated the vibration behavior of an asymmetric rotor under misalignment force. They observed that the maximum amplitude occurs near half of the natural frequency , as a result of asymmetry in the shaft, while the dominant frequency can be seen near when subject to parallel misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [25] investigated the vibration behavior of an asymmetric rotor under misalignment force. They observed that the maximum amplitude occurs near half of the natural frequency , as a result of asymmetry in the shaft, while the dominant frequency can be seen near when subject to parallel misalignment.…”
Section: Introductionmentioning
confidence: 99%